Overall Cultural Competence in the Context of Realization of the Competence Approach - Galina Shpytalevs’ka (Pedagogical Discourse, 2011)
The article analyzes the concept of „overall cultural competence”, addresses issues that relate to the formation of the younger generation in the context of the competence-based approach. It is shown how the focus is in the government documents regarding to the need and importance of the formation of common cultural competency training as a necessary condition for a highly cultured, competent person.